(untitled) (Current Horticulture, 2024)
The field trail was conducted at ICAR- IIHR, Bengaluru to assess the effect of different chemicals (Nitrobenzene @ 1.0 ml, 1.5 ml and 2.0 ml/litre, Cycocel @ 500 ppm, 1000 ppm and 1500 ppm, Uracil @ 25 ppm and 50 ppm, Cycocel @ 1000 ppm + Uracil @ 25 ppm and Cycocel @ 1500 ppm + Uracil @ 50 ppm) on flower induction, fruiting and yield parameters in tissue cultured plant propagules of pomegranate (Punica granatum L.) cv. ’Bhagwa’ during 2016-17 at ICAR-IIHR, Bengaluru. The foliar application of Cycocel @ 1500 ppm gave a significantly increased number of hermaphrodite flowers (287.84) and intermediate flowers (254.14) per plant, thereby increasing the percentage of fruit setting (86.10 %) and number of fruits (156.66) per plant. Thus fruit yield (54.53 kg/plant and 21.81 tonnes/ha), fruit weight (348.32 g), fruit length (8.53 cm) and fruit volume (333.93 ml) increased significantly. Consequently, foliar application of Cycocel @ 1500 ppm led to a significant reduction in number of male flowers (219.70) produced per plant. However, fruit width was non-significant among treatments.